THE INFLUENCE OF TRAINING, EDUCATION AND ASSISTANCE ON UMKM REVENUES IN THE TECHNICAL EXECUTING UNIT (TEU) PLUT OF MICRO AND SMALL AND MEDIUM ENTERPRISES COOPERATIVES SOUTH SULAWESI PROVINCE - Batri, Muhammad (International Journal of Management Progress, 2019)
Micro, Small and Medium Enterprises (MSMEs) in Makassar City are growing and increasing, but there are also some that do not survive the existing problems. This study aims to (1) to determine the effect of training, education and mentoring partially on the income of Micro and Small and Medium Enterprises in the Technical Executing Unit (TEU) PLUT of Micro and Small and Medium Enterprises Cooperatives of South Sulawesi Province; (2) to determine the effect of training, education and assistance simultaneously on the income of Micro and Small and Medium Enterprises in Technical Executing Unit (TEU) PLUT of Micro and Small and Medium Enterprises Cooperatives in South Sulawesi Province (3) to find out the most dominant variables affecting the income of Micro and Small Businesses in Technical Executing Unit (TEU) PLUT of Micro and Small and Medium Enterprises Cooperatives in South Sulawesi Province. The data of this study were obtained through a questionnaire by taking 70 respondents. Analysis of the data used in this study is Multiple Linear Regression using SPSS version 22. The results of this study indicate that the variables of training, education and mentoring have a positive and significant effect partially and simultaneously on the income of Micro and Small and Medium Enterprises in the Technical Executing Unit (TEU) PLUT of Micro and Small and Medium Enterprises Cooperatives in South Sulawesi Province. The most dominant variable influencing the income of Small and Medium Enterprises in Technical Executing Unit (TEU) PLUT of Micro and Small and Medium Enterprises Cooperatives in South Sulawesi Province is 'Training'.